PHENOLOGY AND BIOCHEMICAL COMPOUNDS OF PRUNUS SPINOSA L. FRUITS WITH REGARD TO THE IMPACT OF AIR TEMPERATURE AND PRECIPITATION - Petrov, Djurdja; Čukanović, Jelena D.; Kolarov, Radenka D.; Galečić, Nevenka M.; Skočajić, Dejan Lj.; Vujičić, Dragan G.; Ocokoljić, Mirjana Z. (Journal of Agricultural Sciences (Belgrade), 2025)
Phenology is the study of periodic biological changes that plants undergo, under the influence of geographic and ecological conditions, particularly climatic variables. The aims of the research were to determine the variability of the phenological patterns of Prunus spinosa L. natural populations in the ecotones of the southeastern part of the Balkan Peninsula and to create an informational database regarding the impact of air temperature and precipitation on the phenology of the species, based on research conducted during the period from 2007 to 2024. The obtained data were analysed using descriptive and multivariate statistical methods. The results show that the onset of spring phenological phases has been significantly accelerated by the increase in air temperature, especially in 2024, when flowering started 31 days earlier, the flowering phase was 13 days longer, and fruit ripening occurred 65 days earlier compared to the period 2007–2023. Given that blackthorn significantly contributes to ecosystem services as a honey plant and a species used in the food industry and phytotherapy, the content of phenols, flavonoids, anthocyanins, and antioxidant activity was determined in fruit in distilled water and 70% ethanol. The analysed extracts contain a high percentage of phenols and demonstrate significant antioxidant activity. Based on the conducted research, valuable information was obtained regarding the variability of phenological patterns and the antioxidant capacity of blackthorn fruits, which are important for developing guidelines for ecosystem service conservation programmes, enrichment, and management plans.
Keywords: blackthorn; adaptability; functionality; antioxidant capacity of fruits; ecosystem services; heatwaves; ecotones